The effects of aspirin and fenugreek seed on the testes of white mice - Chaloob, Amal K.; Qasim, Hadeel M.; Gassim, Musheer H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Fenugreek seeds are used as food ingredient in traditional medicines; also aspirin is an incredible chemical with many useful benefits in the medical field. The objective was to study the effect of aspirin and fenugreek on testes of mice. Method: 20 white male mice weighing (18-23gm) were divided into four groups 5 each. Group 1, represented control, group 2, mice treated with fenugreek seed (100mg/KgB.W), group 3 mice treated with aspirin (10mg/Kg B.W), group 4 mice treated with aspirin and fenugreek seed for 21 days. Body weight and testes weights were recorded. Histopathological examination of testes was carried out. Results: a significant decrease (P<0.05) in body weight of mice treated with aspirin when compared to the other groups. A significant decrease (P<0.001) in testicular weight of mice treated with aspirin as compared to control and other groups was noted. Structural changes in testes have shown that: aspirin administration caused a decrease in seminiferous tubules diameter associated with increase in connective tissue between them and basement membrane thickness of seminiferous tubules. While fenugreek seed reverse these changes. Conclusion: fenugreek seeds exhibited antioxidant property that could ameliorate the alternations induced in mice treated with aspirin. Further studies are needed to be done on mammals to support our findings.